Potential Applicability of Cocoa Pulp (Theobroma cacao L) as an Adjunct for Beer Production - Cassiane S. O. Nunes; Marília L. C. da Silva; Geany P. Camilloto; Bruna A. S. Machado; Katharine V. S. Hodel; Maria Gabriela B. Koblitz; Giovani B. M. Carvalho; Ana Paula T. Uetanabaro (The Scientific World Journal)
The aim of this study was to evaluate the application of cocoa pulp as an adjunct for malt in beer production. The cocoa pulp was analyzed for humidity, proteins, lipids, sugars, total soluble solids, organic acids, and minerals. A study was carried out to reduce the cocoa pulp viscosity by enzymatic depectinization, making its use viable in beer production. The cocoa pulp showed relevant quantities of compounds important in fermentation, such as sugars, acids, and minerals. In fermentation using the adjunct, the proportions of pulp used were 10, 30, and 49%. A significant difference was found between the adjunct and all-malt worts. The 30% cocoa pulp concentration as an adjunct for malt in the fermentation medium contributed the most to the fermentative performance of the yeasts at both 15 and 22°C based on the consumption of apparent extract (°Plato), ethanol production, and cellular growth.